Under new management. - Johnston-Watt, Duncan (New York ACM, 2005)
Autonomic computing is revolutionizing the way we manage complex systems.
Keywords: Computing Milieux; Management of computing and information systems; Project and people management; Information systems; Information storage and retrieval; Systems and software; Information interfaces and presentation; Group and organization interfaces; Computing methodologies; Artificial intelligence; Distributed artificial intelligence; Intelligent agents; System management; Design; Management